2017
DOI: 10.1016/s1470-2045(17)30700-3
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete excision of cervical precancer as a predictor of treatment failure: a systematic review and meta-analysis

Abstract: European Federation for Colposcopy and Institut national du Cancer (INCA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
292
5
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(349 citation statements)
references
References 121 publications
42
292
5
10
Order By: Relevance
“…Third, in our series, the only factor that independently correlates with recurrence of high‐grade vaginal intraepithelial neoplasia is HPV persistence after treatment. Although growing evidence suggested that HPV persistence is the most important factor predicting for recurrence in patients having conization for cervical dysplasia , no data support this association in the setting of vaginal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in our series, the only factor that independently correlates with recurrence of high‐grade vaginal intraepithelial neoplasia is HPV persistence after treatment. Although growing evidence suggested that HPV persistence is the most important factor predicting for recurrence in patients having conization for cervical dysplasia , no data support this association in the setting of vaginal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the treatment (excision of the cervical transformation zone) is relatively benign, overtreatment is widely accepted. Obstetric complications are the most important adverse events, but they depend on the depth of excision, and the risk can be safely reduced in most women by performing less deep excisions …”
Section: Strategies For Anal Cancer Screening and Early Detectionmentioning
confidence: 99%
“…Obstetric complications are the most important adverse events, but they depend on the depth of excision, and the risk can be safely reduced in most women by performing less deep excisions. 48,49 An important difference compared with the cervix is that excisions in the anal canal are associated with more adverse outcomes, which can have long-term complications and affect anal sphincter functions. [50][51][52] The decision to treat AIN2/AIN3 and the type of treatment depends on factors such as the size and location of the lesion.…”
Section: Treatment Of Cervical and Anal Precancersmentioning
confidence: 99%
“…In the treatment of HSIL, TCRC resulted not only in lower incidences of positive margins, persistence, and recurrence than did LEEP, but Positive cone margins are an important predictor for CIN persistence/recurrence after conization. [12][13][14] A meta-analysis 15 confirmed that positive cone margins significantly increases the risk of persistence/recurrence. In the present study, TCRC resulted in lower rates of both positive cone margins and persistence/recurrence than did LEEP.…”
Section: Discussionmentioning
confidence: 96%